Violence against married women and its relationship with psychological and social adjustment in Kurdistan - Dr. Jwan Nwri Rasul (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
The general objective of this study is to study the relationship between the level of persecution and psychological and societal empowerment of married women in the Koya city to study the level of persecution of married women at (100) women after obtaining some information through direct encounter and using the closed questionnaire of the level of persecution consisting of 60 paragraphs After the implementation of the research model and using the methods of statistical analysis it was found that there are no significant differences (0.096) at (0.34) between the level of violence and psychological and societal empowerment and the result was that the level of analysis of violence (77.53) and deviation (22) was the result (200.25) (30.7) and using ((T.test) we found variable violence is a moral as well as the effect of psychological mastery is significant but there are no significant differences between the relationship between the psychological and societal mastery at the level of (0.05).